Diagnosis and Management of Vitamin D Dependent Rickets - Levine, Michael A. (Frontiers in Pediatrics, 2020)
The term "vitamin D dependent rickets" describes a group of genetic disorders that are characterized by early-onset rickets due to the inability to maintain adequate concentrations of active forms of vitamin D or a failure to respond fully to activated vitamin D. Although the term is now admittedly a pathophysiological misnomer, there remains clinical relevance for its continued use, as patients have a lifelong "dependency" on administration of specialized regimens of vitamin D replacement. This review provides an update on the molecular bases for the three forms of vitamin D dependent rickets, and summarizes current protocols for management of affected subjects.